2020
DOI: 10.24272/j.issn.2095-8137.2020.088
|View full text |Cite
|
Sign up to set email alerts
|

Age-associated changes in amyloid-β and formaldehyde concentrations in cerebrospinal fluid of rhesus monkeys

Abstract: A: Intergroup analyses of Aβ 40 concentrations. B: Intergroup analyses of Aβ 42 concentrations. C: Intergroup analyses of FA concentrations. D: Correlation between CSF Aβ 40 and FA concentrations in young group ( R =–0.3385, P =0.2172). E: Correlation between CSF Aβ 40 and FA concentrations in middle-aged group ( R =0.02914,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…These animals not only develop tau pathology but also amyloid plaques that are a hallmark of AD. We and others have demonstrated this pathology in animals of similar age to the cohort examined in this study ( Mufson et al, 1994 ; Paspalas et al, 2018 ; Li et al, 2020 ). Recent analysis of a subset of our aging monkey cohort revealed age-related elevations in calcium-cAMP-PKA signaling in dlPFC ( Datta et al, 2021 ).…”
Section: Discussionsupporting
confidence: 76%
“…These animals not only develop tau pathology but also amyloid plaques that are a hallmark of AD. We and others have demonstrated this pathology in animals of similar age to the cohort examined in this study ( Mufson et al, 1994 ; Paspalas et al, 2018 ; Li et al, 2020 ). Recent analysis of a subset of our aging monkey cohort revealed age-related elevations in calcium-cAMP-PKA signaling in dlPFC ( Datta et al, 2021 ).…”
Section: Discussionsupporting
confidence: 76%
“…Rhesus macaque share many common structural, physiology, immunity and heredity traits with humans [ 9 ]. For example, the homology of the nucleic acid sequence between macaques and humans was reported to be more than 95% [ 10 ]; hence, rhesus monkeys are important experimental animals in scientific research [ 11 , 12 , 13 ]. In recent years, the passenger flow at the Mount Emei scenic spot has increased rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…This could be due to differences in assays, as we used a Luminex multiplex (Millipore, USA) while they used individual ELISA kits for each biomarker (ImmunoBiological Laboratories, Japan). In another study done by Li et al, CSF was obtained by LP and Aβ40 and Aβ42 were measured in young (n = 15), middle-aged (n = 22), and aged (n = 19) groups 31 . Their reported values were quite similar to ours, and Aβ40 values ranged from approximately 1000-3300 pg/ml and Aβ42 ranged from 100-800 pg/ml 31 .…”
Section: Relation To Previous Nhp Studiesmentioning
confidence: 99%
“…With this caveat, our results indicating that Aβ biomarkers decrease with age in female rhesus is consistent with other published data. A few studies with limited sample sizes have revealed a significant decrease with age in CSF Aβ40 levels in both male and female aged cynomolgus and rhesus macaques 24,31 and also Aβ42 31 . On the other hand, Zhao et al report no change in Aβ40, but an increase in Aβ42 with aged rhesus macaques 25 .…”
Section: Relation To Previous Nhp Studiesmentioning
confidence: 99%